2017
DOI: 10.56093/ijas.v87i7.71946
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence analysis in gladiolus (Gladiolus grandiflorus)

Abstract: The present investigation was carried out to assess the extent of genetic variability, heritability, genetic advance and genetic divergence using 33 gladiolus (Gladiolus grandiflorus Hort) genotypes with 16 characters. Moderate to high GCV and PCV were recorded for almost all the characters under study emphasizing the existence of variation in the population. All the characters (except number of days required for spike initiation, number of days required for first floret opening and number of florets/spike) sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In contrast, low coefficient of variation for TBF, SL, FW, AL, TL and TW suggested that the genetic uniformity of genotypes for these traits is due to their homozygous nature. earlier findings suggested that time required for flowering in gladiolus is heritable and also genetically controlled (Ranjan et al 2010;Taloh 2014).…”
Section: Phenotypic Characterization Based On Dus Descriptorsmentioning
confidence: 99%
“…In contrast, low coefficient of variation for TBF, SL, FW, AL, TL and TW suggested that the genetic uniformity of genotypes for these traits is due to their homozygous nature. earlier findings suggested that time required for flowering in gladiolus is heritable and also genetically controlled (Ranjan et al 2010;Taloh 2014).…”
Section: Phenotypic Characterization Based On Dus Descriptorsmentioning
confidence: 99%
“…Bacillus subtilis and Pseudomonas fluorescens were assessed against F. solani by dual culture technique at 27±2 °C. [12] , Walid et al…”
Section: In Vitro Efficacy Of Bioagents Against Fusarium Solanimentioning
confidence: 99%